40 Caring for carers: a social worker and nurse-led hospice model. Issue 3 (1st September 2017) - Thomas, Glyn; Harris, Louise; Thomas, Liz; Davidson, Jason; Gishen, Faye
Abstract : Introduction: Marie Curie recognises the contribution that carers make to the support and wellbeing of those diagnosed with terminal illness. 1 Their 2012 report highlighted a lack of support for carers as well as the associated negative social and economic impact of caring for a dying relative. The Carers UK Report, 2014 2 found that nearly 6000 people become carers every day, with £1.1 billion of Carers' Allowance going unclaimed each year. Aims: The understanding and appreciation of challenges faced by carers led to the establishment of a dedicated Carers' Clinic at Marie Curie Hospice, Hampstead, London in April 2016. The aim was to support carers, with the focus on answering their questions and addressing their concerns. Methods: The model was social worker and nurse-led. A modified version of the Carers Support Needs Assessment Tool (CSNAT) was used as the basis for the consultation 3 and a questionnaire evaluation was completed following the clinic appointment. Results: Between April 2016 and March 2017 there were 31 consultations with 23 evaluations completed. Both quantitative and qualitative data was captured. 83% of respondents said that the clinic met their needs. Many carers requested follow-up sessions. The key themes identified were around financial advice, carers' health needs and support with managing their relatives' illness. Conclusion: The Carers Clinic is now established in the hospice. Further developments include the establishment of a new service enabling carers to be referred for six sessions of pre-bereavement support, as well as a plan to implement an 8 week mindfulness programme. References: . Marie Curie (2012) Committed to Carers; Supporting Carers of People at the End of Life, Marie Curie. pp.4-5, 7-8, 11–12 . Carers UK (2014) Need to know; Transitions in and out of Caring: The Information Challenge . Carers UK. pp.4. . Ewing, G & Grande, G. (2013) Development of a Carer Support Needs Assessment Tool (CSNAT ) for End-of-Life Care Practice at Home: A Qualitative Study . Palliative Medicine; 27 (3) pp.244–256.